Prophylaxis of peripartum haemorrhage using recombinant factor VIIa (rfVIIa) in pregnant women with congenital factor VII deficiency: A case report and literature review. (April 2019) - Loddo, Alessandro; Cornacchia, Stefania; Cane, Fiorenza Lo; Barcellona, Doris; Marongiu, Francesco; Melis, Gian Benedetto; Angioni, Stefano; Paoletti, Anna Maria; Neri, Manuela
Abstract: Congenital factor VII deficiency is a rare autosomal recessive disorder associated to different haemorrhagic manifestations. Labour and delivery may cause bleeding risk in patients with this coagulation deficit, thus it is appropriate to clarify whether prophylaxis of peripartum haemorrhage is necessary. To date, there are very few cases in scientific literature which report the management of women with congenital factor VII deficiency during labour, and a consensus for prophylaxis does not exist. In this manuscript we present the management of a 35 years old woman with factor VII deficiency, treated with recombinant factor VIIa before delivery, without haemorrhagic complications either for the woman and for the infant. Therefore, we present a review of similar cases managed with a peripartum prophylaxis with recombinant factor VIIa, and discuss its usefulness and effectiveness, in view of the severity of the deficit and the doses used.